2011
DOI: 10.1128/jvi.00035-11
|View full text |Cite
|
Sign up to set email alerts
|

Baculovirus VP80 Protein and the F-Actin Cytoskeleton Interact and Connect the Viral Replication Factory with the Nuclear Periphery

Abstract: Recently, we showed that the Autographa californica multicapsid nucleopolyhedrovirus (AcMNPV) VP80 protein is essential for the formation of both virion types, budded virus (BV) and occlusion-derived virus (ODV). Deletion of the vp80 gene did not affect assembly of nucleocapsids. However, these nucleocapsids were not able to migrate from the virogenic stroma to the nuclear periphery. In the current paper, we constructed a baculovirus recombinant with enhanced-green fluorescent protein (EGFP)-tagged VP80, allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
83
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 62 publications
0
83
0
1
Order By: Relevance
“…Since the interaction between 38K and VP1054 has been demonstrated previously (35) and since PP78/83 does not locate in the nucleus without BV/ ODV-C42 (31), in the present study we investigated primarily whether VP1054 interacts with BV/ODV-C42 or VP39. In addition, VP80 is a nuclear F-actin-related capsid protein that is required for transport of mature nucleocapsids (55), and both VP80 and VP1054 were proved to interact with 38K (35). So we also investigated whether VP1054 interacts with VP80.…”
Section: Resultsmentioning
confidence: 99%
“…Since the interaction between 38K and VP1054 has been demonstrated previously (35) and since PP78/83 does not locate in the nucleus without BV/ ODV-C42 (31), in the present study we investigated primarily whether VP1054 interacts with BV/ODV-C42 or VP39. In addition, VP80 is a nuclear F-actin-related capsid protein that is required for transport of mature nucleocapsids (55), and both VP80 and VP1054 were proved to interact with 38K (35). So we also investigated whether VP1054 interacts with VP80.…”
Section: Resultsmentioning
confidence: 99%
“…During the early stages of infection, a virusinduced specific nuclear region appears, the VS, which is thought to be the active site for viral DNA replication, condensation and packaging into capsids (Fraser, 1986). The newly formed nucleocapsids are transported from the VS to the ring zone region periphery of the inner nuclear membrane and then egress from the nucleus to form BVs in the early stage of infection, or acquire envelopes from intranuclear microvesicles to form ODVs in the late stage of infection (Marek et al, 2011). In the present study, masses of aberrant capsid structures were observed in vBmP95-De-transfected cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that P6.9 (Wang et al, 2010a), VP39 (Thiem & Miller, 1989), VP1054 (Olszewski & Miller, 1997), P78/83 , VLF-1 (Vanarsdall et al, 2006), FP25 (Braunagel et al, 1999(Braunagel et al, , 2001, BV/ODV-C42 (Braunagel et al, 2001), ODV-EC27 , vp80 (Marek et al, 2011), P24 (Wolgamot et al, 1993), AC141 (EXON0; Fang et al, 2007), AC142 (McCarthy et al, 2008) and AC98 (38K; Wu et al, 2008) are associated with BV and ODV nucleocapsids. P95, a homologue of Ac83 of Autographa californica multicapsid nucleopolyhedrovirus (AcMNPV), is a virion capsid protein of both BV and ODV and was originally characterized as VP91 in Orgyia pseudotsugata MNPV (OpMNPV; .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the coupling of the DNAbinding function of VP80 to virus morphogenesis has not been established yet. VP80 contains an atypical basic helix-loop-helix (bHLH) DNA-binding domain at its essential C-terminal end (18) and N-terminally located paramyosin-like motifs, likely responsible for the experimentally shown association of VP80 with host nuclear filamentous actin (F-actin) (17). Furthermore, VP80 has been previously shown to interact with 38K, another nucleocapsid-associated protein (19).…”
mentioning
confidence: 99%
“…In addition to the above-mentioned VP39, there are a number of minor, but functionally important, capsid-associated proteins (see references 1, 2, and 15 for reviews), which may play essential roles in both recognition of target DNA and its packaging. Among these capsid-associated proteins are two end-linked proteins, very late factor 1 (VLF-1) (16) and VP80 (17,18), which exhibit DNA-binding activities. VLF-1 is a site-specific recombinase and is likely implicated in postreplication processing of viral DNA preceding its packaging (16).…”
mentioning
confidence: 99%